Irisin and the Metabolic Phenotype of Adults with Prader-Willi Syndrome - Hirsch, Harry J. (PLoS One, 2015)
CONTEXT: Hyperphagia, low resting energy expenditure, and abnormal body composition contribute to severe obesity in Prader Willi syndrome (PWS). Irisin, a circulating myokine, stimulates “browning” of white adipose tissue resulting in increased energy expenditure and improved insulin sensitivity. Irisin has not been previously studied in PWS. OBJECTIVES: Compare plasma and salivary irisin in PWS adults and normal controls. Examine the relationship of irisin to insulin sensitivity and plasma lipids. DESIGN AND STUDY PARTICIPANTS: A fasting blood sample for glucose, lipids, insulin, leptin, adinopectin, and irisin was obtained from 22 PWS adults and 54 healthy BMI-matched volunteers. Saliva was collected for irisin assay in PWS and controls. RESULTS: Fasting glucose (77±9 vs 83±7mg/dl, p = 0.004), insulin (4.1±2.0 vs 7.9±4.7μU/ml, p<0.001), and triglycerides (74±34 vs 109±71mg/dl, p = 0.007) were lower in PWS than in controls. Insulin resistance (HOMA-IR) was lower (0.79±0.041 vs 1.63±1.02, p<0.001) and insulin sensitivity (QUICKI) was higher (0.41±0.04 vs 0.36±0.03, p<0.001) in PWS. Plasma irisin was similar in both groups, but salivary irisin (64.5±52.0 vs 33.0±12.1ng/ml), plasma leptin (33.5±24.2 vs 19.7±19.3ng/ml) and plasma adinopectin (13.0±10.8 vs 7.6±4.5μg/ml) were significantly greater in PWS (p<0.001). In PWS, plasma irisin showed positive Pearson correlations with total cholesterol (r = 0.58, p = 0.005), LDL-cholesterol (r = 0.59, p = 0.004), and leptin (r = 0.43, p = 0.045). Salivary irisin correlated negatively with HDL-cholesterol (r = -0.50, p = 0.043) and positively with LDL-cholesterol (r = 0.51, p = 0.037) and triglycerides (r = 0.50, p = 0.041). CONCLUSIONS: Salivary irisin was markedly elevated in PWS although plasma irisin was similar to levels in controls. Significant associations with plasma lipids suggest that irisin may contribute to the metabolic phenotype of PWS.